A pioneering genotypic and phylogenetic characterisation of Cichorium crops through a genome-scale sequencing for future breeding innovations - Francesco Scariolo; Samela Draga; Damiano Riommi; Alessandra Tondello; Lydia Grace Griffin; Fabio Palumbo; Alessandro Vannozzi; Gianni Barcaccia (BMC Plant Biology)
Abstract The genus Cichorium, which comprises economically important crops such as chicory and endive, exhibits significant genetic and phenotypic diversity. This study used genome-scale sequencing based on ddRAD technology to explore the genetic diversity and relationships, and to identify multiple discriminant loci within this genus. Moreover, microscopy analysis was conducted to identify morphological traits, such as pappus structure, to aid species-level identifications. Despite this, the genetic complexity within Cichorium remains challenging to resolve based solely on phenotypic characteristics. Our study confirms the efficacy of ddRADseq in generating high-quality genotyping-by-sequencing data, identifying 1,350 multi-allelic polymorphic loci across 368 genotypes and revealing significant genetic differentiation among species, varieties, and biotypes. Lower observed heterozygosity (Ho) compared to expected heterozygosity (Hs) suggests the presence of fixed genotypes within biotype groups, likely due to selection for specific morphological traits. Genetic distance and clustering analyses proved the distinctiveness of self-incompatible species (C. intybus and C. spinosum) from self-compatible species (C. endivia and C. pumilum). Notably, a strong genetic relationship was observed between C. intybus var. foliosum (Witloof) and var. sativum (Root chicory), supporting the hypothesis of a common ancestry. These findings may help refine the taxonomic classification of Cichorium, offering valuable insights for the conservation of genetic resources and their classification, the precise adoption in breeding decisions and genomic selection of suitable genotypes, as well as the genotypic identity determination of registered cultivars with the protection of breeder’s rights.